Challenges of Inclusion of Almagirai in Nigerian School Feeding Scheme - Umar, Abubakar Saidu; Jongur Umar DAHIRU; Aliyu ABDULLAHI (RADINKA JAYA UTAMA PUBLISHER, 2024)
Almagirci has recently become an ideological battlefield debate about the roles of government to support them, which sometimes often focuses on feeding. It is expected that all children should equally attain the highest standard of education and nutrition through a school feeding scheme, but in the context of Nigeria, the commitment is different, especially for Almajirai. This study aims to examine the likely challenges in including Almagirai in Nigerian school feeding schemes with an emphasis on people's perceptions. The use of a survey research method through a questionnaire was adopted by the researchers, administered in Mubi North and South local government area of Adamawa State, Nigeria. The survey area represents only two out of hundreds of local governments in the country where Almajirai are sited. The findings revealed that out of 220 respondents, 166 (75.45%) and 174 (79.09%) strongly disagree with the current situation of Almajirai in terms of their feeding and the government commitments toward Almagiranci respectively. It was also revealed that 188 (85.45%) of respondents strongly agreed and in support of governments to include Almajirai in the school feeding scheme, simultaneously, 198 (90.00%) respondents responded that the inclusion will have a positive impact on their learning. In response to these challenges, It is expected that governments should move urgently to bring Almagirai under their oversight and regulation to enable her to take care of nutrition and the standard of their education.